Optimal pricing scheme for addictive goods - Eleftheria Triviza (The RAND Journal of Economics, 2024)
Abstract This article analyses how consumers' habit formation and addiction affect firms' pricing policies. I consider both sophisticated consumers, who realize that their current consumption will affect future tastes, and “naive” consumers, who do not. The optimal contract for sophisticated consumers is a two-part tariff. The main result is that the optimal pricing pattern when the consumer is naive is a “bargain then rip-off” contract, namely a fixed fee, with the first units priced below cost, and then priced above marginal cost. This holds both under symmetric and asymmetric information about the consumers' degree of~sophistication.
Keywords: 330; addiction; habit formation; non-linear pricing; naivety